2012
DOI: 10.1002/app.37567
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization of a curing thermoset epoxy‐anhydride system—Isothermal and nonisothermal cure kinetics

Abstract: This work describes in detail the kinetic model for the cure of an epoxy-anhydride thermoset matrix resin system. The cure kinetics in both nonisothermal and isothermal modes has been characterized using differential scanning calorimetry. The Sestak-Berggren two-parameter autocatalytic model was used to describe the nonisothermal cure behavior of the resin satisfactorily. The isothermal cure data was fitted with Kamal's four-parameter autocatalytic model, coupled with a diffusion factor. These characterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…This, on one side, makes the model quite complex, on the other side is logically suspicious even if mathematically right. In earlier studies, the average values from the developed data sets from each cure curves are taken as a general model . However, the model based on the average value seems to predict the curing behavior poorly, as shown in Figures and .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This, on one side, makes the model quite complex, on the other side is logically suspicious even if mathematically right. In earlier studies, the average values from the developed data sets from each cure curves are taken as a general model . However, the model based on the average value seems to predict the curing behavior poorly, as shown in Figures and .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Kissinger method simplifies the activation energy and pre‐exponential factor as being a constant value during the whole reaction, which possible could be an over‐simplification for complex reactions. However, this method is applied in many studies for kinetic analysis of epoxy systems and reported to be a feasible estimation of the model starting parameter …”
Section: Theoriotical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations